การศึกษาและวิเคราะห์คุณลักษณะทางแสงของหลอดไดโอดเปล่งแสงในระบบทางหลวง (STUDY AND ANALYSIS LUMINESCENCE CHARACTERISTICS OF LIGHT-EMITTING DIODE FOR THE HIGHWAY) - อยู่มาก, สัณฐิติ; เง่าพิทักษ์กุล, อรรถพล (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2015)
งานวิจัยฉบับนี้นำเสนอการศึกษาและวิเคราะห์การจำลองระบบแสงสว่างเพื่อเปรียบเทียบคุณภาพแสงสว่างของโคมไฟชนิดหลอดโซเดียมความดันไอสูง (HPS) 250 วัตต์ กับ โคมไฟชนิดหลอดไดโอดเปล่งแสง (LED) 120 วัตต์ ในกรณีรูปแบบของถนนมีเกาะกลางและถนนไม่มีเกาะกลาง และทำการปรับปรุงคุณภาพแสงสว่างจากโคมไฟชนิดหลอดไดโอดเปล่งแสงให้อยู่ในเกณฑ์มาตรฐานของกรมทางหลวง ด้วยวิธีการจำลองปรับลดความสูงเสาไฟถนนและระยะห่างระหว่างเสาไฟถนน ผลจากการจำลองพบว่า โคมไฟชนิดหลอดไดโอดเปล่งแสงมีประสิทธิภาพความสว่างต่ำกว่าโคมไฟชนิดหลอดโซเดียมความดันไอสูง ส่วนการปรับลดความสูงของเสาไฟถนนและระยะห่างระหว่างเสาไฟถนนมีผลทำให้ค่าความสว่างเฉลี่ยเพิ่มขึ้น แต่การลดความสูงของเสาไฟถนนจะทำให้ค่าความสม่ำเสมอแสงลดต่ำลงแตกต่างจากวิธีลดระยะห่างระหว่างเสาซึ่งจะทำให้ค่าความสม่ำเสมอแสงดีขึ้น คำสำคัญ: หลอดโซเดียมความดันไอสูง หลอดไดโอดเปล่งแสง ค่าความสว่าง ค่าความสม่ำเสมอ This paper presents the study and analysis lighting system by simulation and comparison lighting parameter between high pressure sodium (HPS) lamps 250 watt and the light emitting diode (LED) lamps 120 watts. Two case studies have been done, the first case is road lighting without street isle and the second one is road lighting with street isle. To improve the quality of lighting emitting diode lamp, Department of Highways of Thailand regulation must be considered. The simulation of this research are focus on two factors, one is height of pole and another one is distance between the two poles. The results showed that light emitting diode lamps have less efficiency than high pressure sodium lamps. Average illuminance can be increased due to reducing height of poles and distance between the two poles but reducing height of pole make low uniform of illuminance different from reducing distance between the two pole. Keywords: High pressure sodium luminaire, Light-emitting diode luminaire, Illuminance, Uniformity